Is peer review in decline? - Ellison, Glenn 1965- (Working paper series / National Bureau of Economic Research, 2007)
Over the past decade there has been a decline in the fraction of papers in top economics journals written by economists from the highest-ranked economics departments. This paper documents this fact and uses additional data on publications and citations to assess various potential explanations. Several observations are consistent with the hypothesis that the Internet improves the ability of high-profile authors to disseminate their research without going through the traditional peer-review process.